2021
DOI: 10.3390/jcm10153315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Dexamethasone-Eluting Electrode Array on the Post-Implant Cochlear Fibrotic Reaction by Three-Dimensional Immunofluorescence Analysis in Mongolian Gerbil Cochlea

Abstract: Cochlear implant is the method of choice for the rehabilitation of severe to profound sensorineural hearing loss. The study of the tissue response to cochlear implantation and the prevention of post-cochlear-implant damages are areas of interest in hearing protection research. The objective was to assess the efficacy of dexamethasone-eluting electrode array on endo canal fibrosis formation by three-dimensional immunofluorescence analysis in implanted Mongolian gerbil cochlea. Two trials were conducted after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Seventeen studies 3,5,10,22,27–39 used animal models. These studies were published between 2008 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies 3,5,10,22,27–39 used animal models. These studies were published between 2008 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…For all these aspects, advancements in cochlear implant design and surgical techniques will greatly improve the efficiency of optical stimulation. For example, studies involving release of corticosteroids in the cochlea have shown promising results towards decreasing formation of scar tissue [57] , [58] , [59] . Perimodiolar (or “modiolus-hugging”) implants, which are designed to lie in closer proximity to the SGNs, provide more reliable stimulation with less spectral spread [60] , [61] .…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy to mitigate the cochlear tissue response to implanted electrode arrays is to delivery pharmaceuticals that modulate cellular responses. For example, electrode arrays that elute dexamethasone are currently under development in an effort to limit intracochlear tissue fibrosis (Farhadi et al, 2013;Toulemonde et al, 2021). Further studies are needed to explore strategies to limit the FBR to implanted biomaterials and improve hearing outcomes for CI recipients.…”
Section: Discussionmentioning
confidence: 99%